CRITICAL THINKING AND MATHEMATICAL PROBLEM-SOLVING SKILLS USING PROBLEM-BASED AND PROJECT-BASED LEARNING MODELS AMONG EIGHTH-GRADE STUDENTS AT SMP NEGERI 20 REJANG LEBONG - Warniati Warniati; Risnanosanti Risnanosanti; Tomi Hidayat (Journal of Research in Social Science and Humanities, 2026)
This study aims to analyze the differences and effects of problem-based learning, project-based learning, and direct instruction models on students’ critical thinking and mathematical problem-solving abilities. The research employed a quasi-experimental design with a pretest–posttest control group design. The population of the study consisted of all eighth-grade students of SMP Negeri 20 Rejang Lebong in the 2025/2026 academic year, totaling 83 students, and all were used as the sample through a total sampling technique. The research instruments were essay tests measuring critical thinking skills and mathematical problem-solving abilities, which had been tested for validity and reliability. Data analysis was conducted through normality tests, homogeneity tests, and one-way ANOVA with a significance level of 0.05. The results showed that the average posttest score of critical thinking ability in the project-based learning class (86) was higher than that in the problem-based learning class (83) and the direct instruction class (76). In terms of problem-solving ability, the highest average score was obtained by the problem-based learning class (87), followed by the project-based learning class (86) and the direct instruction class (81). The ANOVA test results indicated a significance value of 0.05, demonstrating that there are significant differences and effects among the three learning models on both abilities. It can be concluded that problem-based learning and project-based learning models are more effective than direct instruction in improving students’ critical thinking and mathematical problem-solving abilities